Peran Literasi Keuangan, Perbedaan Gender dan Inklusi Keuangan terhadap Kapabilitas Pemasaran UMKM: Financial Literacy, Gender Differences and Financial Inclusion, Marketing Capability of MSMEs - Olii, Nurhayati; Nanggong, Ardiwansyah (Benefit: Jurnal Manajemen dan Bisnis, 2022)
MSMEs as an economic sector which very vulnerable to financial problems and are dominated by home industries that are attributable to gender stereotypes in their management. Consequently, the dynamics of its management become quite complex in enhancing their marketing capabilities. The purpose of this study to investigate the impact of financial literacy, gender differences, and financial inclusion on leveraging the marketing capabilities of MSMEs. Collecting data using a survey questionnaire on 168 MSMEs in Gorontalo City with a merge of accidental and snowball sampling techniques. Data analysis using binary logistic regression. The results reveal that the existence of financial knowledge has a significant impact on the creation of financial inclusion in micro, small and medium enterprises. Furthermore, there are different patterns for women and men in obtaining access to credit. The role of gender differences in men who are more likely to access inclusive financial services than women. On the other hand, the creation of financial inclusion further enhances the marketing capabilities of MSMEs.